Microrganismos e substâncias húmicas no enraizamento de estacas de cultivares de oliveira - Ritter, Giovana (2019)
The production of seedlings in olive growing is mainly due to the cutting method, but it is still necessary to improve the process. Considering that, the objective of the present work was to evaluate the rooting of olive cuttings with inoculation of microorganisms and humic substances and its best form of application. Four experiments were carried out, the first two occurred from October / 17 to January / 18 and they evaluated the rooting of cuttings of four cultivars (Koroneiki, Ascolano, Picual and Maria da Fé). In the first experiment the cuttings were inoculated with three species of arbuscular mycorrhizal fungi (FMAs - Gigaspora margarita, Glomus clarum and Glomus etunicatum) plus control, and in the second one the rooting of the four cultivars inoculated with four doses (0, 25, 50 and 75 mL L-1) of commercial inoculant Nitro 1000® containing Azospirillum brasilense. The experimental design used in the first two experiments was randomized blocks in a 4 x 4 factorial scheme. The other two experiments were carried out from November / 18 to February / 19, evaluating the rooting of cuttings of the cultivars Maria da Fé and Ascolano. The third experiment consisted of 4 applications and 5 treatments (T1 - commercial product SoloHumics ®, T2 - humic acid, T3 - fulvic acid, T4 - peat residual water and T5 - control) in cuttings previously treated with 3000 mg L - 1 of AIB. The experimental design used in the third experiment was randomized blocks, in a 2 x 5 factorial scheme. The fourth experiment consisted in rooting the same cultivars of experiment 3, with 3 forms of application of the commercial product SoloHumics® (stake immersion, irrigation of the substrate) + control (AIB). The experimental design of the fourth experiment was randomized blocks, in a 2 x 4 factorial scheme. Evaluations occurred 75 days after assembly of the experiments, measuring the percentage of rooted cuttings, callus and sprouts, number and length of shoots, length of the largest root. The use of AMF in the cultivars Maria da Fé and Picual has a positive response to cutting rooting and the fungi benefit the quality of the seedlings by the higher number of shoots and larger root length. The relation Azospirillum brasilense / cultivar is specific, behaving differently among the genotypes, and the Picual cultivar does not respond to inoculation of the bacterium having less viability in the propagation by cutting. Maria da Fé has the best rooting percentages with the use of inoculant dose up to 75 mL L-1 and Koroneiki with 55 mL L-1 of inoculant. The cuttings of the cultivar Ascolano 315 presented the best rooting in the treatment with humic acids. The commercial product favored a greater average length of the highest root for the Maria da Fé cultivar and the fulvic acids favored Ascolano 315. The best method of application of humic substances occurred in the form of bed irrigation for the cultivar Maria da Fé.